In search of an osteoblast cell model for in vitro research - EM Czekanska; MJ Stoddart; RG Richards; JS Hayes (European Cells & Materials, 2012)
The process of bone formation, remodelling and healing involves a coordinated action of various cell types. Advances in understanding the biology of osteoblast cells during these processes have been enabled through the use of various in vitro culture models from different origins. In an era of intensive bone tissue engineering research, these cell models are more and more often applied due to limited availability of primary human osteoblast cells. While they are a helpful tool in developing novel therapies or biomaterials; concerns arise regarding their phenotypic state and differences in relation to primary human osteoblast cells. In this review we discuss the osteoblastic development of some of the available cell models; such as primary human, rat, mouse, bovine, ovine and rabbit osteoblast cells; as well as MC3T3-E1, MG-63 and SaOs-2 cell lines, together with their advantages and disadvantages. Through this, we provide suggestions on the selection of the appropriate and most relevant osteoblast model for in vitro studies, with specific emphasis on cell-material based studies.